2015
DOI: 10.1186/s13014-015-0398-4
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-Modulated Radiotherapy (IMRT) vs Helical Tomotherapy (HT) in Concurrent Chemoradiotherapy (CRT) for Patients with Anal Canal Carcinoma (ACC): an analysis of dose distribution and toxicities

Abstract: PurposeIntensity-modulated radiotherapy (IMRT) and helical tomotherapy (HT) have been adopted for radiotherapy treatment of anal canal carcinoma (ACC) due to better conformality, dose homogeneity and normal-tissue sparing compared to 3D-CRT. To date, only one published study compares dosimetric parameters of IMRT vs HT in ACC, but there are no published data comparing toxicities. Our objectives were to compare dosimetry and toxicities between these modalities.Methods and materialsThis is a retrospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The advent of new therapies, more and more personalized to the patients and the recent improvements of neoadjuvant therapies, radiotherapy and chemotherapy can cause a down staging of the lesion, such as to make operable lesions that were not resectable before treatment [ 12 14 ]. In addition, the choice of low-invasive surgery, with sphinter saving technique, increases the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of new therapies, more and more personalized to the patients and the recent improvements of neoadjuvant therapies, radiotherapy and chemotherapy can cause a down staging of the lesion, such as to make operable lesions that were not resectable before treatment [ 12 14 ]. In addition, the choice of low-invasive surgery, with sphinter saving technique, increases the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 12 , 13 ] On the contrary, a delays in diagnosis might lead to an advance cancer stage at presentation with worst survival, [ 8 ]. The recent improvements of neoadjuvant therapies, radiotherapy and chemotherapy, can also down staging the lesion, as well as to allow a conservative treatment [ 9 – 14 ]. According to National Comprehensive Cancer Network (NCCN) Anal Carcinoma Guidelines the patients should be subjected to a careful clinical examination, including a digital rectal examination (DRE), an anoscopic examination, and palpation of inguinal nodes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This combination allows for a more precise definition of the planning target volume (PTV) and accurate irradiation. Dosimetric studies have shown that HT could reduce the doses delivered to the normal tissues in patients affected by lower gastrointestinal cancers (i.e., locally advanced rectal cancer or anal cancers) when compared with conventional 3D- conformal RT (De Bari et al 2018 ; Yang et al 2013 ) or IMRT (Yeung et al 2015 ). Clinical data on the role of HT in the treatment of locally advanced rectal cancer are available, but is mainly in the form of a small study which consisted of only a small cohort of 36 patients (Huang et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mitomycin C lacks preferential selectivity for hypoxic cells; and, in clinical trials, it was administered once or twice during a radiotherapy course. [101] The ARO 95-06 randomized trial compared hyperfractionated accelerated chemoradiation with mitomycin C/5-fluorouracil (C-HART) with hyperfractionated accelerated radiation therapy (HART) alone in locally advanced head-and-neck cancer. Long-term results showed that C-HART remains superior to HART in terms of locoregional control and survival rates.…”
Section: Chemical Radiosensitizersmentioning
confidence: 99%